Plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating as well as preparation method and application thereof
A plasma spraying method for preparing NiCoCrAlY metal bonding layer, gradient transition layer and La2Zr2O7 ceramic layer on high-temperature alloy substrate has solved the problem of coating cracking caused by thermal expansion coefficient mismatch, realized high-performance thermal barrier coating, significantly improved thermal shock life and thermal insulation performance, and is suitable for high-temperature components of aero-engines.
Patent Information
- Application Number
- CN202511176277.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2025-11-28
AI Technical Summary
The existing double-layer La2Zr2O7/NiCoCrAlY thermal barrier coating is prone to high interfacial thermal stress due to thermal expansion coefficient mismatch under high temperature environment, which leads to coating cracking, peeling failure, and failure. Moreover, the existing gradient structure design has not effectively improved the metal/ceramic interface mismatch problem, affecting thermal shock life.
A La2Zr2O7/NiCoCrAlY gradient thermal barrier coating was prepared by plasma spraying. The coating structure consists of a NiCoCrAlY metal binder layer, a gradient transition layer, and a La2Zr2O7 ceramic layer from the substrate to the surface. Nanoscale γ' precipitates are dispersed in the NiCoCrAlY metal phase in the gradient transition layer. The multilayer gradient design alleviates CTE mismatch and optimizes stress distribution.
It significantly improves the thermal shock resistance and service life of the coating, reduces thermal stress, and increases the thermal shock life to 8 times that of traditional double-layer structures, while maintaining good thermal insulation performance. It is suitable for high-temperature alloy components such as turbine blades of aero-engines.
Smart Images

Figure CN121023409A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of high-temperature protective coating, and particularly relates to a thermal barrier coating (TBCs) for high-temperature alloy components, in particular, a La2Zr2O7 (LZO) / NiCoCrAlY (NAY) thermal barrier coating with a multi-layer gradient transition structure and a plasma spraying preparation method thereof and application in improving the thermal shock resistance of high-temperature alloys. BACKGROUND
[0002] High-temperature alloys are widely used in the fields of aerospace, petroleum, etc., especially in the field of aero-engine, more than 50% of turbine blades use high-temperature alloys. After a long period of development, nickel-based alloys occupy an extremely important position in high-temperature alloy materials. At present, GH4169 alloy is one of the most widely used nickel-based high-temperature alloys in the field of aerospace.
[0003] With the improvement of the performance of aerospace engines, the working environment of high-temperature components thereof is increasingly severe, which puts forward higher requirements for the performance of thermal barrier coatings (TBCs). The traditional double-layer structure TBCs (ceramic layer + metal bonding layer) are prone to produce huge thermal stress at the interface during thermal cycling due to the significant difference in the coefficient of thermal expansion (CTE) between the ceramic layer and the metal bonding layer, resulting in coating cracking, peeling and failure, and limited service life. Especially for new ceramic materials with higher melting point and lower thermal conductivity such as La2Zr2O7, the CTE mismatch problem with the bonding layer is more prominent. In order to alleviate the CTE mismatch problem, the functionally graded structure TBCs reduce the interfacial stress by continuous or step change of composition, which is an effective way to improve the thermal shock resistance, but the structure design, preparation process and performance optimization still need further research. Moreover, the existing technology can only improve the thermal shock resistance life of the thermal barrier coating system by preparing a double-ceramic layer gradient coating with continuous composition change at the ceramic / ceramic interface, but this structure cannot fundamentally improve the metal / ceramic interface mismatch problem.
[0004] In addition, although plasma spraying has the advantages of high efficiency, relatively low cost and the ability to prepare complex-shaped components, in the application of this technology, the specific process and coating structure design for high-performance LZO / NAY gradient thermal barrier coating, especially with a multi-layer fine gradient transition structure to improve the thermal shock resistance life, still need further research. SUMMARY
[0005] The purpose of the present application is to overcome the shortcomings of the existing double-layer structure LZO / NAY TBCs, such as poor thermal shock resistance and easy failure, and the deficiencies of the existing gradient structure design in significantly improving the thermal shock life and optimizing the stress distribution, and to provide an LZO / NAY gradient thermal barrier coating with excellent thermal shock resistance, low residual stress, good thermal insulation and easy industrialization, and a preparation method thereof.
[0006] The objective of this invention is achieved through the following means:
[0007] A plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating, wherein the gradient thermal barrier coating is deposited on a high-temperature alloy substrate, and the coating structure comprises, from the substrate to the surface, the following components in sequence:
[0008] A NiCoCrAlY (NAY) metal bonding layer adjacent to the substrate; a gradient transition layer above the metal bonding layer; and a La2Zr2O7 (LZO) ceramic layer on the outermost layer of the gradient transition layer.
[0009] The gradient transition layer comprises NiCoCrAlY and La2Zr2O7, and nanoscale γ' precipitates are dispersedly distributed in the NiCoCrAlY metallic phase of the gradient transition layer.
[0010] Preferably, the gradient transition layer has two or more transition layers, and the mass ratio of NiCoCrAlY to La2Zr2O7 in each layer changes continuously from the metal binder layer to the ceramic surface layer along the coating thickness direction. Preferably, this change is a stepwise decrease (i.e., the LZO content increases).
[0011] Preferably, the high-temperature alloy is GH4169 alloy.
[0012] Preferably, the thickness of the metal bonding layer is 100 μm ± 25, the thickness of the La2Zr2O7 ceramic layer is 100 μm ± 25, and the thickness of each transition layer in the gradient transition layer is 100 μm ± 25.
[0013] Preferably, the plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating comprises five layers from the substrate to the surface: a first layer (bottom layer) of 100% NAY as a binder; a second layer of a mixture of 70% NAY and 30% LZO; a third layer of a mixture of 50% NAY and 50% LZO; a fourth layer of a mixture of 30% NAY and 70% LZO; and a fifth layer (outermost layer) of 100% LZO ceramic. There are no obvious macroscopic interfaces between the layers, and the ceramic phase is distributed in a gradient within the coating matrix.
[0014] Preferably, the NiCoCrAlY metallic phase in the third layer contains a dispersed nanoscale γ' precipitate, and most preferably, a dispersed nanoscale γ' precipitate with a size of about 16 nm.
[0015] The method for preparing the plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating includes the following steps:
[0016] (1) Matrix pretreatment: The surface of the high-temperature alloy matrix GH4169 is ultrasonically cleaned and roughened by sandblasting (to improve the bonding force);
[0017] (2) Powder preparation: NiCoCrAlY powder and La2Zr2O7 powder were mixed at mass ratios of 70:30, 50:50 and 30:70 respectively, and dried after high-energy ball milling; wherein, the ball-to-material ratio was 10-15:1, the rotation speed was 200-400 r / min; high-purity ethanol was used as the process control agent;
[0018] (3) Plasma spraying is performed on the substrate in the order from substrate to surface, and the plasma spraying conditions are as follows:
[0019] 100% NiCoCrAlY binder coating: current 450A, Ar gas flow rate 57SLPM, H2 gas flow rate 8.5SLPM, powder feeding speed 15g / min, spraying distance 150mm, spray gun speed 600mm / s;
[0020] Gradient layer spraying: Ar gas flow rate 57 SLPM, H2 gas flow rate 8.5 SLPM, spray gun travel speed 600 mm / s;
[0021] The specific layered spraying process, following the sequence of 70NAY / 30LZO → 50NAY / 50LZO → 30NAY / 70LZO, is as follows:
[0022] 30% NAY + 70% LZO layer: current 550A, powder feeding speed 15g / min, spraying distance 100mm;
[0023] 50% NAY + 50% LZO layer: current 550A, powder feeding speed 15g / min, spraying distance 100mm;
[0024] 70% NAY + 30% LZO layer: current 550A, powder feeding speed 12g / min, spraying distance 100mm;
[0025] 100% La2Zr2O7 ceramic layer spraying: current 550A, Ar flow rate 57SLPM, H2 flow rate 8.5SLPM, powder feed rate 20g / min, spraying distance 90mm, spray gun speed 600mm / s.
[0026] Preferably, the NAY powder has an average particle size of 40-105 μm, and the LZO powder has an average particle size of 30-80 μm.
[0027] Preferably, the high-temperature alloy matrix is GH4169 nickel-based alloy, which undergoes solution aging heat treatment before spraying. The treatment involves solution aging at 960℃ for 1-1.5 hours, followed by air cooling to room temperature; aging at 720℃ for 7.5-8.5 hours, followed by furnace cooling to 620℃; and aging at 620℃ for 7.5-8.5 hours, followed by air cooling to room temperature.
[0028] The La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating applied by atmospheric plasma spraying can be used on the surface of high-temperature alloys.
[0029] The advantages of this invention compared with the prior art are as follows:
[0030] (1) The present invention adopts a unique gradient structure design to alleviate the CTE mismatch problem to the greatest extent, significantly reducing the maximum tensile stress, tensile and compressive stress amplitude and interface stress change during thermal shock, and increasing the thermal shock life of the LZO / NAY system to 8 times that of the traditional double layer.
[0031] (2) The gradient design has little effect on the low thermal conductivity advantage of the LZO ceramic layer, and the coating still has excellent thermal insulation performance.
[0032] (3) During the preparation of the gradient layer, the high spraying temperature (550A current) induces NAY metal. The NAY particles are equivalent to aging during the solidification and cooling process, which promotes the precipitation of γ' and significantly improves the high temperature strength and thermal stability of the coating.
[0033] (4) The high-performance gradient LZO / NAY TBCs of the present invention are particularly suitable for high-temperature components of advanced aero-engines with extremely high requirements for thermal shock life, such as turbine blades, and can significantly improve their service reliability and service life. Attached Figure Description
[0034] Figure 1 The diagrams show two-layer, three-layer gradient, and five-layer gradient thermal barrier coatings. The gradient thermal barrier coating designs are as follows: (a) two-layer coating, (b) three-layer gradient coating, and (c) five-layer gradient coating.
[0035] Figure 2 The cross-sectional morphology of the five-layer gradient thermal barrier coating is shown in the figure. (a) Overall SEM image, (b) SEM image of the ceramic layer, (c) SEM image of the gradient layer, and (d) SEM image of the adhesive layer.
[0036] Figure 3 EBSD analysis of the cross-section of a five-layer gradient thermal barrier coating is shown. In the figure, (a) is the IPF diagram, (b) is the phase distribution diagram, and (c) is the KAM diagram.
[0037] Figure 4TEM image of the LZO / NAY interface in the gradient layer (50% NAY + 50% LZO) (showing the γ' precipitate and the amorphous layer at the interface).
[0038] Figure 5 The figures show cross-sectional views of a five-layer gradient thermal barrier coating. In the figures, (a) and (b) are thermally shocked 6 times, (c) and (d) are thermally shocked 13 times, and (e) and (f) are thermally shocked 24 times.
[0039] Figure 6 Oxidative weight gain at 1000℃ was measured for three different thermal barrier coating structures.
[0040] Figure 7 The figures show the residual stress variations for coatings with different structures. In the figures, (a), (b), and (c) represent axial stress, and (d), (e), and (f) represent radial stress. Detailed Implementation
[0041] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0042] In the specific embodiments of the present invention, unless otherwise specified, the reagents and materials used are all conventional commercially available products in the art and can be obtained through commercial channels.
[0043] Example 1: Preparation of a five-layer La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating
[0044] 1. Matrix preparation: GH4169 nickel-based high-temperature alloy was selected and subjected to solution aging heat treatment: solution treatment at 960℃ for 1 hour, followed by air cooling to room temperature; aging at 720℃ for 8 hours, followed by furnace cooling to 620℃; aging at 620℃ for 8 hours, followed by air cooling to room temperature; wire cutting into samples of the required size of 50*100mm.
[0045] 2. Surface pretreatment: Use an ultrasonic cleaner to remove oil, particles and other impurities from the sample surface, then roughen the sample surface with sandblasting, and then clean the sample surface again.
[0046] 3. Powder preparation: NiCoCrAlY powder and La2Zr2O7 powder were mixed at mass ratios of 70:30, 50:50, and 30:70, respectively, and then dried after high-energy ball milling; wherein the ball-to-powder ratio was 15:1, the rotation speed was 300 r / min; high-purity ethanol was used as the process control agent; the average particle size of the NAY powder was 40-105 μm, and the average particle size of the LZO powder was 30-80 μm.
[0047] 4. Plasma Spraying (Equipment: Metco F4MB-XL spray gun): Plasma spraying is performed sequentially on the substrate, from substrate to surface. The thermal spraying process parameters for the metal bonding layer are shown in Table 1. The selected Ar and H2 gas flow rates for the gradient layer and ceramic layer are consistent with those for the metal bonding layer. The remaining process parameters are shown in Table 2. The gradient thermal barrier coating design is as follows: Figure 1 5. Post-processing: After the coating is completed, the coating sample is cut into 15mm diameter round pieces, which can be used directly for testing.
[0048] Table 1. Process parameters for plasma spraying of NiCoCrAlY metal bonding layer
[0049]
[0050] Table 2. Process parameters for plasma spraying gradient layer and ceramic layer
[0051]
[0052] Example 2:
[0053] The remaining steps and corresponding parameters are the same as in Example 1, except that a thermal barrier coating with a three-layer gradient coating structure (3-LC: NAY adhesive layer + 50% NAY / 50% LZO gradient layer + LZO ceramic layer) is prepared. After spraying, the coating sample is cut into circular pieces with a diameter of 15 mm.
[0054] Example 3:
[0055] The remaining steps and corresponding parameters are the same as in Example 1, except that there is no gradient coating, resulting in a thermal barrier coating with a double-layer structure (2-LC: NAY adhesive layer + LZO ceramic layer). After spraying, the coating sample is cut into 15mm diameter discs.
[0056] Experimental Example 1:
[0057] The performance of the five-layer gradient coating (5-LC) sample prepared in Example 1, the three-layer gradient coating (3-LC, structure: NAY binder layer + 50% NAY / 50% LZO gradient layer + LZO ceramic layer) sample prepared in Example 2, and the conventional two-layer coating (2-LC, structure: NAY binder layer + LZO ceramic layer) sample prepared in Example 3 were tested. The specific steps are as follows:
[0058] 1. Microstructure observation of coatings: The microstructure of La2Zr2O7, NiCoCrAlY and powders mixed in different proportions were analyzed using scanning electron microscopy (SEM), and the composition of the powders was analyzed using the energy dispersive X-ray spectroscopy (EDS) instrument built into the SEM.
[0059] The surface and cross-section microstructure of the three different thermal barrier coatings were analyzed using scanning electron microscopy, electron backscatter diffraction (EBSD), and transmission electron microscopy (TEM). Samples used for TEM observation were prepared using focused ion beam (FIB). To observe and analyze the microstructure of the coating cross-section, the sample cross-section was mounted, then polished, impurities were removed using an ultrasonic cleaner, and finally dried for later use.
[0060] 2. Thermal Shock Resistance Test of Coating: The thermal shock resistance of the thermal barrier coating was tested according to industry standard JB / T7703-95, using a thermal cycling test method at 1200℃. Before the thermal shock test, all coating surfaces were photographed and weighed. After the resistance furnace reached 1200℃, the coating was placed in the furnace and held for 5 minutes, then removed and water-cooled. After drying, the surface was photographed and weighed to observe coating peeling. If the peeling area was less than 20%, the previous step was repeated, and the coating was kept at the same temperature until the peeling area was greater than 20%. After the experiment, the cross-section of the coating after thermal shock was analyzed by SEM and compared with the cross-sectional morphology before thermal shock. The mass change data recorded in the experiment were plotted as a curve to analyze the mechanism of thermal shock failure of the coating.
[0061] 3. High-Temperature Oxidation Performance Test: Before the isothermal oxidation experiment, the crucibles were preheated to constant weight. One type of coating was placed in each crucible, and the total mass of the sample and crucible was weighed and recorded using an electronic balance. After preheating the resistance furnace to 1000℃, three groups of coatings with different numbers of layers were placed in the furnace for heat preservation. Three groups were placed in total, and one group of samples was taken out, weighed, and recorded every 20, 50, and 100 hours. After the experiment, SEM technology was used to characterize the morphology and compositional changes of the coating cross-section before and after oxidation, and the anti-oxidation mechanism of the coating was analyzed in conjunction with the coating oxidation kinetic curves.
[0062] 4. Finite element simulation: The thermal insulation performance of thermal barrier coatings with different structures and the distribution of thermal stress during thermal shock were simulated and analyzed using Ansys Workbench finite element software. A model corresponding to the actual coating was established, and the material parameters (Table 3) were input to simulate the temperature field and stress field in the thermal insulation performance (steady-state heat conduction) and thermal shock process (transient thermal stress coupling).
[0063] Experimental results:
[0064] 1. Figure 2 This indicates that in the five-layer gradient thermal barrier coating of Example 1, there are almost no obvious pores at the interface between the gradient layer and the adhesive layer, resulting in high bonding strength. Figure 3The EBSD analysis results for the cross-section of the five-layer thermal barrier coating show that the ceramic phase grain size remains consistently small in both the ceramic layer and the gradient layer, without any growth. This indicates that the five-layer thermal barrier coating exhibits better resistance to thermal expansion and improved thermal stability, allowing for prolonged use in high-temperature environments. Furthermore, in the five-layer gradient coating, the NAY grain size in the binder layer is significantly smaller than that in the three-layer gradient thermal barrier coating, contributing to the coating's superior resistance to thermal expansion and thermal stability. Figure 4 The TEM morphology at the interface between LZO and NAY in the gradient transition layer shows that there are a large number of dispersed circular γ' phases with a size of about 16 nm in the NAY of the surface gradient layer, which play a role in precipitation strengthening.
[0065] 2. In thermal shock performance testing, the 2-LC failed after only 3 cycles (the entire ceramic layer detached); the 3-LC failed after 18 cycles; and the 5-LC failed after 24 cycles. The thermal shock life of the 5-LC is 8 times that of the 2-LC and 33.3% higher than that of the 3-LC. Figure 5 As can be seen in c, a large transverse crack appeared at the interface between the LZO ceramic layer and the gradient layer. When the gradient transition layer is magnified locally, no obvious transverse cracks are observed.
[0066] 3. Cross-sections were observed after the coatings were oxidized in static air at 1000℃ for different times (20h, 50h, 100h). Oxidation was not significant for any structure after 20h. After 50h, 2-LC showed a thick TGO (>20μm) and detached entirely; 3-LC and 5-LC also showed TGO, but it was thinner, and the structure was well preserved. After 100h, the TGO in 3-LC and 5-LC thickened and cracks appeared. Figure 6 The oxidation weight gain curves show that the gradient structures (3-LC and 5-LC) have similar effects on oxidation behavior.
[0067] 4. The thermal insulation performance and thermal stress of three different structural coatings were compared and analyzed using the finite element method. Figure 7 The stress comparison shows that the axial stress of the double-layer thermal barrier coating has a large stress change in both the metal bonding layer and the ceramic layer. However, the thermal barrier coating with a gradient structure has a lower internal stress. The gradient structure can effectively alleviate the stress change caused by the difference in thermal expansion coefficients between the bonding layer and the ceramic layer, reduce the stress extreme value in the coating, and has minimal impact on the thermal insulation performance.
[0068] Therefore, this invention provides a high-performance La2Zr2O7 / NiCoCrAlY five-layer gradient thermal barrier coating and its optimized atmospheric plasma spraying preparation method. Through a rational gradient structure design (NAY->70 / 30->50 / 50->30 / 70->LZO) and a specific spraying process (especially 550A current-induced γ' phase precipitation), this coating achieves an effective transition in the coefficient of thermal expansion between the ceramic layer and the bonding layer, significantly reducing thermal stress and stress concentration during thermal shock, and increasing the thermal shock resistance life to eight times that of traditional double-layer structures, while maintaining good thermal insulation performance and microstructural integrity. This coating is particularly suitable for high-temperature components of advanced aero-engines and has significant engineering application value.
[0069] Table 3 Physical parameters of coating materials
[0070]
Claims
1. A plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating, characterized in that, The gradient thermal barrier coating is deposited on a high-temperature alloy substrate, and the coating structure, from the substrate to the surface, comprises: A NiCoCrAlY metal bonding layer adjacent to the substrate; a gradient transition layer above the metal bonding layer; and a La2Zr2O7 ceramic layer on the outermost layer of the gradient transition layer. The gradient transition layer comprises NiCoCrAlY and La2Zr2O7, and nanoscale γ' precipitates are dispersedly distributed in the NiCoCrAlY metallic phase of the gradient transition layer.
2. The plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating according to claim 1, wherein the gradient transition layer has two or more transition layers, and the mass ratio of NiCoCrAlY to La2Zr2O7 in each layer changes gradient from the metal bonding layer to the ceramic surface layer along the coating thickness direction.
3. The plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating according to claim 2, characterized in that, The thickness of the metal bonding layer is 100μm±25, the thickness of the La2Zr2O7 ceramic layer is 100μm±25, and the thickness of each transition layer in the gradient transition layer is 100μm±25.
4. The plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating according to claim 1, comprising five layers sequentially from the substrate to the surface, specifically including: The first layer is a 100% NiCoCrAlY bonding layer; Second layer: a mixed layer of 70% NiCoCrAlY and 30% La2Zr2O7; Third layer: a mixed layer of 50% NiCoCrAlY and 50% La2Zr2O7; Fourth layer: a mixed layer of 30% NiCoCrAlY and 70% La2Zr2O7; The fifth layer is a 100% La2Zr2O7 ceramic layer.
5. The plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating according to claim 1, characterized in that, The third layer of NiCoCrAlY metallic phase contains nanoscale γ' precipitates dispersedly.
6. A method for preparing a plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating as described in claim 1, characterized in that... The preparation method includes the following steps: (1) Pretreatment of the substrate: The surface of the high-temperature alloy substrate GH4169 was ultrasonically cleaned and roughened by sandblasting; (2) Powder preparation: NiCoCrAlY powder and La2Zr2O7 powder were mixed at mass ratios of 70:30, 50:50 and 30:70 respectively, and dried after high-energy ball milling; wherein the ball-to-material ratio was 10-15:1 and the rotation speed was 200-400 r / min; (3) Plasma spraying is performed on the substrate in the order from substrate to surface, and the plasma spraying conditions are as follows: 100% NiCoCrAlY binder coating: current 450A, Ar gas flow rate 57SLPM, H2 gas flow rate 8.5SLPM, powder feeding speed 15g / min, spraying distance 150mm, spray gun speed 600mm / s; Gradient layer spraying: Ar gas flow rate 57 SLPM, H2 gas flow rate 8.5 SLPM, spray gun travel speed 600 mm / s; The specific layering spraying process, following the sequence of 70NiCoCrAlY / 30La2Zr2O7, 50NiCoCrAlY / 50La2Zr2O7, and 30NiCoCrAlY / 70La2Zr2O7, is as follows: 70% NiCoCrAlY and 30% La2Zr2O7 mixed layer: current 550A, powder feeding speed 12g / min, spraying distance 100mm; 50% NiCoCrAlY and 50% La2Zr2O7 mixed layer: current 550A, powder feeding speed 15g / min, spraying distance 100mm; 30% NiCoCrAlY and 70% La2Zr2O7 mixed layer: current 550A, powder feeding speed 15g / min, spraying distance 100mm; 100% La2Zr2O7 ceramic layer spraying: current 550A, Ar flow rate 57SLPM, H2 flow rate 8.5SLPM, powder feed rate 20g / min, spraying distance 90mm, spray gun speed 600mm / s.
7. The method for preparing the plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating according to claim 6, characterized in that... The average particle size of the NiCoCrAlY powder is 40-105 μm, and the average particle size of the La2Zr2O7 powder is 30-80 μm.
8. The preparation method according to claim 6, characterized in that: The high-temperature alloy matrix is GH4169 nickel-based alloy, which undergoes solution aging heat treatment before pretreatment.
9. The preparation method according to claim 6, characterized in that... The solution aging heat treatment is as follows: solution treatment at 960℃ for 1-1.5 hours, followed by air cooling to room temperature; aging at 720℃ for 7.5-8.5 hours, followed by furnace cooling to 620℃; and aging at 620℃ for 7.5-8.5 hours, followed by air cooling to room temperature.
10. The application of the plasma-sprayed La2Zr2O7 / NiCoCrAlY gradient thermal barrier coating as described in claim 1 on the surface of high-temperature alloys.